2011
DOI: 10.5851/kosfa.2011.31.5.649
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Kimchi Powder on the Quality Properties of Emulsion Type Sausage Made with Irradiated Pork Meat

Abstract: In this study, the effects of kimchi powder on the quality properties of an emulsion type sausage made with irradiated pork meat were investigated. Raw ground pork ham was gamma-irradiated at 5 and 10 kGy, and the emulsion type sausage was then manufactured with the irradiated pork meat. The pH value was shown to increase by irradiation of raw material (p<0.05). Samples containing kimchi powder had a lower pH value than other treatments, but no significant differences were observed. In a sensory evaluation, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…The Vapor Print (polar graphs of kimchi) frequency pattern was obtained by differentiation of frequency chromatograms and transformation into cycles based on total retention time. The images were formed by transforming the time variable to a radial angle with the beginning and end of the analysis occurring at 0° or vertical . The results of polar graphs of peaks showed that the addition of baking soda or heat‐treated baking soda influenced the various flavor patterns.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Vapor Print (polar graphs of kimchi) frequency pattern was obtained by differentiation of frequency chromatograms and transformation into cycles based on total retention time. The images were formed by transforming the time variable to a radial angle with the beginning and end of the analysis occurring at 0° or vertical . The results of polar graphs of peaks showed that the addition of baking soda or heat‐treated baking soda influenced the various flavor patterns.…”
Section: Resultsmentioning
confidence: 99%
“…Although the electronic nose is sensitive for obtaining smell information of samples, slight changes in volatile compounds may result in differences in sensor responses . Therefore, quantitative analysis, such as GC/MS, is additionally necessary.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential use of plasma protein hydrolysates as functional ingredients for the preparation of sausages is considered to investigate the effect of the inclusion of these hydrolysates on the physico-chemical and sensory properties of boiled sausages [43].…”
Section: Introductionmentioning
confidence: 99%